Integrated monitoring of enveloped viruses in hospital environments: Detection, persistence, and implications for infection control - Yalda Hashempour; Mohammad-Ali Zazouli; Nematallah Jaafarzadeh; Reza Valadan; Soheila Golchin; Zabihollah Yousefi; Ramzan-Ali Dianati; Ali Atamaleki; Fatemeh Mortezazadeh; Atefeh Jabari (PLoS ONE, 2026)
Enveloped viruses, including coronaviruses, influenza viruses, and others, pose significant public health risks due to their ability to persist in various environments. This study investigates the persistence of enveloped viruses, particularly SARS-CoV-2, in three key environments: air, surfaces, and wastewater, with a focus on hospital settings. We present a systematic review of the literature on the environmental persistence of these viruses, complemented by a case study conducted in two reference hospitals in northern Iran. A total of 72 wastewater samples, 46 air samples, and 92 surface samples were collected from COVID-19 wards and analyzed using RT-PCR for the presence of viral RNA. Results indicate notable viral persistence, with detection rates of 21.74% in air samples, 26.09% in surface samples, and 63.89% in wastewater samples. This indicates substantial viral shedding from infected patients, particularly in influent samples, where treatment inefficiency contributed to higher detection. It is important to note that RT-PCR detects viral RNA, which does not necessarily indicate infectivity; however, its presence highlights routes of potential transmission and the need for vigilant environmental management. The findings highlight the critical need for enhanced environmental monitoring and the strict implementation of effective disinfection protocols to mitigate the risk of viral transmission in healthcare settings. The persistence of SARS-CoV-2 in hospital environments underscores the importance of addressing fomite transmission and optimizing ventilation strategies. Overall, this comprehensive approach provides valuable insights into the behavior of enveloped viruses in diverse settings and emphasizes the necessity of integrated surveillance strategies to aid infection control efforts and protect public health.